Faktor-Faktor Yang Berhubungan Dengan Kesiapan Psikologis Ibu Primigravida Pada Kelas Ibu Hamil Di Puskesmas Ratu Agung Kota Bengkulu - Jumita Jumita; Ekasari YP; Harlyanita Harlyanita; Lezi Yovita Sari (JMNS, 2021)
Complicated anxiety and feeling in pregnant women can have a negative impact on both the mother and the fetus from pregnancy to delivery. Mothers who have readiness to overcome childbirth will be able to pass the assessment comfortably, and be better prepared to face childbirth. The purpose of this study was to study the factors related to the psychological readiness of primigravidian mothers in the class of pregnant women in the work area of Ratu Agung Kota Bengkulu Health Center in 2019. The type of research used was an analytical survey using Cross Sectional design. The population in this study were pregnant women who took classes in pregnant women at the Ratu Agung Health Center in January 2019 as many as 124 people, of which 80 were primigravida pregnant women. Sampling was carried out using a total sampling technique of 80 primigravida pregnant women. From the results of the study, there is a relationship between preparations with primigravida psychological mothers, there is a relationship between education and psychological preparations of primigravida mothers, there is a relationship between knowledge with psychological preparations of primigravida mothers, there is a relationship between families with primigravida psychological help, the most important factor to reject The psychological preparation of the primigravida mother is family assistance. Suggestion: mothers can increase their knowledge and routinely attend every activity related to the assessment and preparation of labor.